Lactobacillus acidophilus novel strain, MJCD175, as a potential probiotic for oral health in dogs - You, Inhwan; Mahiddine, Feriel Yasmine; Park, Heekee; Kim, Min Jung (Frontiers in Veterinary Science, 2022)
The oral cavity is the second-largest habitat for microorganisms, and a well-balanced oral microbiome contributes to preventing dental disorders caused by pathogenic bacteria. Since humans and dogs have different lifestyles and oral microbiome structures, the present study aimed to develop novel probiotics for dogs. A total 53 Lactobacillus spp. were isolated from healthy dogs, and nine isolates were identified as Lactobacillus acidophilus according to 16S rRNA gene sequencing. According to the high antimicrobial activity against the dental caries-causing bacterium Streptococcus mutans, single or three mixed strains were orally administered to dogs for four weeks with concentration of 108 to 109 CFU/day. Intraoral swab samples were collected before and after the administration, and changes of oral pathogen were analyzed using quantitative PCR. Among them, Porphyromonas gingivalis, a critical factor of periodontitis, was significantly reduced in the single-strain administered group. Based on the acid and bile salts tolerance characteristics of isolates, systemic effects were also analyzed by comparing serum immunoglobulin and reproductive ability before and after the administration. However, no significant changes were observed in the serum IgG level and sperm quality. Overall, these in vitro and in vivo results suggest that L. acidophilus isolates from dogs, especially L. acidophilus MJCD175, could be promising probiotic candidates to support oral health without systemic adverse effects in dogs.